Bridging Gaps: Cross-Sector Collaboration in Improving Sanitation Access in Last-Miles Communities of South Sulawesi, Indonesia - Muh. Saleh; Wildan Setiabudi; Andi Bunga Tongeng; Hamsah Sinring; Nildawati Nildawati; Ain Khaer; Muhammad Rachmat (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
ntroduction: According to the Global Burden of Disease study, approximately 775,000 lives were lost prematurely in 2017 due to poor sanitation. In 2020, only 54% of the global population had access to safely managed sanitation. Therefore, this study aimed to explore cross-sector collaboration for improving sanitation access at